2008
DOI: 10.1177/1753193408087116
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Row Carpectomy Versus Four-Corner Arthrodesis as a Treatment for SLAC (Scapholunate Advanced Collapse) Wrist

Abstract: Four-corner arthrodesis and proximal row carpectomy are motion-preserving salvage solutions for the scapholunate advanced collapse wrist. We compared both procedures in a non-randomised, retrospective study of 30 cases with a mean follow-up of 3(1/2) years. Pain relief and functional gain were equal in both treatment groups. However, the complication rate was higher in the four-corner arthrodesis group, partly because of the need for internal fixation. The higher incidence of carpal tunnel syndrome following f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 22 publications
2
48
0
2
Order By: Relevance
“…Severe pain was absent in our study, where the patients were basically able to perform their daily activities, without needing further carpal arthrodesis. Furthermore, a recent study found that the rate of complications such as carpal tunnel syndrome was higher and the duration of hospital stay was longer in the arthrodesis group [16]. We thus believe that proximal row carpectomy should be preferred if both procedures are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Severe pain was absent in our study, where the patients were basically able to perform their daily activities, without needing further carpal arthrodesis. Furthermore, a recent study found that the rate of complications such as carpal tunnel syndrome was higher and the duration of hospital stay was longer in the arthrodesis group [16]. We thus believe that proximal row carpectomy should be preferred if both procedures are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Vanhove et al 37 wrist arthrodesis and noted better outcomes with PRC. Dacho et al 38 preferred PRC for patients who required less grip strength at work.…”
Section: Studies Comparing Prc With 4-corner Arthrodesismentioning
confidence: 95%
“…Note that several studies show mildly better motion after PRC than after scaphoidectomy with 4CF, 1,[13][14][15][16][17] although not all studies support this distinction. 18,19 One clear difference between PRC and scaphoidectomy with 4CF is the complication rate needed for postoperative immobilization: complications were significantly more common after scaphoidectomy with 4CF, including nonunion, delayed union, and hardware-related problems, and the period of immobilization is greater for scaphoidectomy with 4CF. 12 In patients who cannot tolerate an extended period of wrist immobilization, or in heavy smokers in whom nonunion is a concern, PRC may be preferred.…”
Section: Four-corner Arthrodesis Versus Proximal Row Carpectomymentioning
confidence: 99%